Lucia Coppolaro y Francine McKenzie (Eds.). A Global History of Trade and Conflict since 1500. London, Palgrave-McMillan, 2013, 252 págs., ISBN: 978-1-137-32682-9. - Fernández de Pinedo, Nadia (Investigaciones de Historia Económica, 2019)
Sin resumen